The Influence of Product Variety, Price, Promotion, and Service Quality on Repurchase Interest in Raja Kebab and Rantauprapat Burger Culinary Delights - Armada. S, Kiki; Nasution, Siti Lam’ah; Syaputra, Rizky (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This study aims to analyze the effect of product variations, prices, promotions, and service quality on repurchase interest. The type of research used is explanatory research with an accidental sampling technique. The number of samples set is 100 respondents. Data analysis in this study used SPSS version 22 software. The results showed that product variations affected repurchase interest, price influenced repurchase interest, promotions influenced repurchase interest, and service quality influenced repurchase interest. Simultaneously, product variation, price, promotion, and service quality affect repurchase interest.